Glycogen Metabolism and Rheumatoid Arthritis: The Role of Glycogen Synthase 1 in Regulation of Synovial Inflammation via Blocking AMP-Activated Protein Kinase Activation - Shi, Maohua; Wang, Jingnan; Xiao, Youjun; Wang, Cuicui; Qiu, Qian; Lao, Minxi; Yu, Yangtao; Li, Zhifeng; Zhang, Hongwei; Ye, Yujin; Liang, Liuqin; Yang, Xiuyan; et al. (Frontiers in Immunology, 2018)
Objective To investigate the role of glycogen metabolism in regulating rheumatoid fibroblast-like synoviocyte (FLS)-mediated synovial inflammation and its underlying mechanism. Methods FLSs were separated from synovial tissues obtained from Rheumatoid arthritis (RA) patients. Glycogen content was determined by Periodic acid Schiff staining. Protein expression was analyzed by Western blot or immunohistochemistry. Gene expression of cytokines and matrix metalloproteinases (MMPs) was evaluated by qRT-PCR. FLS proliferation was detected by EdU incorporation. Migration and invasion were measured by Boyden chamber assay. Results Glycogen levels and GYS1 expression were significantly increased in the synovial tissue and FLSs of RA patients. TNF-α or hypoxia induced GYS1 expression and glycogen synthesis in RA FLSs. GYS1 knockdown by shRNA decreased the expression of IL-1β, IL-6, CCL-2, MMP-1 and MMP-9 and proliferation and migration by increasing AMP-activated protein kinase (AMPK) activity in RA FLS. AMPK inhibitor or knockdown AMPK could reverse the inhibitory effect of GYS1 knockdown on the inflammatory response in RA FLSs; however, an AMPK agonist blocked RA FLS activity. We further determined that HIF-1α mediates TNF-α- or hypoxia-induced GYS1 expression and glycogen levels. Local joint depletion of GYS1 or intraperitoneal administration with an AMPK agonist ameliorated the severity of arthritis in rats with CIA. Conclusions Our data demonstrate that GYS1-mediated glycogen accumulation contributes to FLS-mediated synovial inflammation in RA by blocking AMPK activation. In our knowledge, this is a first study linking glycogen metabolism to chronic inflammation. Inhibition of GYS1 might be a novel therapeutic strategy for chronic inflammatory arthritis, including RA.